Contemporary challenges to the laws of war : essays in honour of Professor Peter Rowe - Rowe, P. J. (Peter J.); Harvey, Caroline, 1977-; Summers, James, 1974-; White, Nigel D., 1961- (Cambridge University Press, 2014)
"The laws of war are facing new challenges from emerging technologies and changing methods of warfare, as well as the growth of human rights and international criminal law. International mechanisms of accountability have increased and international criminal law has greater relevance in the calculations of political and military leaders, yet perpetrators often remain at large and the laws of war raise numerous normative, structural and systemic issues and problems. This edited collection brings together leading academic, military and professional experts to examine the key issues for the continuing role and relevance of the laws of war in the twenty-first century. Marking Professor Peter Rowe's contribution to the subject, this book re-examines the purposes of the laws of war and asks whether existing laws found in treaties and customs work to achieve these purposes and, if not, whether they can they be fixed by specific reforms or wholesale revision"--